Genome of Linum usitatissimum convar. crepitans expands the view on the section Linum - Dvorianinova, Ekaterina M.; Pushkova, Elena N.; Bolsheva, Nadezhda L.; Borkhert, Elena V.; Rozhmina, Tatiana A.; Zhernova, Daiana A.; Novakovskiy, Roman O.; Turba, Anastasia A.; Sigova, Elizaveta A.; Melnikova, Nataliya V.; Dmitriev, Alexey A. (Frontiers in Genetics, 2023)
Sequencing whole plant genomes provides a solid foundation for applied and basic studies. Genome sequences of agricultural plants attract special attention, as they reveal information on the regulation of beneficial plant traits. Flax is a valuable crop cultivated for oil and fiber. Genome sequences of its representatives are rich sources of genetic information for the improvement of cultivated forms of the plant. In our work, we sequenced the first genome of flax with the dehiscence of capsules—Linum usitatissimum convar. сrepitans (Boenn.) Dumort—on the Oxford Nanopore Technologies (ONT) and Illumina platforms. We obtained 23 Gb of raw ONT data and 89 M of 150 + 150 paired-end Illumina reads and tested different tools for genome assembly and polishing. The genome assembly produced according to the Canu—Racon ×2—medaka—POLCA scheme had optimal contiguity and completeness: assembly length—412.6 Mb, N50—5.2 Mb, L50—28, and complete BUSCO—94.6% (64.0% duplicated, eudicots_odb10). The obtained high-quality genome assembly of L. usitatissimum convar. crepitans provides opportunities for further studies of evolution, domestication, and genome regulation in the section Linum.